Attitudes Towards the Legal Context of Unsafe Abortion in Timor-Leste - Belton, S.; Whittaker, A.; Fonseca, Z.; Wells-Brown, T.; Pais, P. (2012)
The new Penal Code in 2009 was an opportunity for Timor-Leste to allow some legal grounds for abortion, which was highly restricted under Indonesian rule. Public debate was contentious before ratification of the new code, which allowed abortion to Save G women's life and health. A month later, 13 amendments to the code were passed, highly restricting abortion again. This paper describes the socio-legal context of unsafe abortion in Timor-Leste, based on research in 2006-08 on national lows and policies Grid interviews with legal professionals, police, doctors and midwives, and community-based focus group discussions. Data on unsafe abortions in Timor-Leste ore rarely recorded. A small number Of Cases of abortion and infanticide ore reported but are rarely prosecuted, due to deficiencies in evidence and procedure. While there are voices supporting low reform, the Roman Catholic church heavily influences public policy and opinion. Professional views on when abortion should be legal varied, but in the community people believed that saving women's lives was paramount and come before the law. The revised Penal Code is insufficient to reduce unsafe abortion and maternal mortality. Change will be slow, but access to safe abortion and modern contraception ore crucial to women's ability to participate fully as citizens in Timor-Leste. (C) 2009 Reproductive Health Matters. All rights reserved.